Liquefaction experiment and analysis projects (LEAP): Summary of observations from the planning phase. Issue 113 (October 2018) - Manzari, Majid T.; Ghoraiby, Mohamed El; Kutter, Bruce L.; Zeghal, Mourad; Abdoun, Tarek; Arduino, Pedro; Armstrong, Richard J.; Beaty, Michael; Carey, Trevor; Chen, Yunmin; Ghofrani, Alborz; Gutierrez, David; et al.
Abstract: The LEAP international collaboratory is introduced and its key objectives and main accomplishments during the planning phase of the US-LEAP (LEAP-2015) are presented. The main theme of LEAP-2015 was lateral spreading of sloping liquefiable soils. A summary of the results of the laboratory element tests performed on the selected soil (Ottawa F-65) is presented. The numerical simulations submitted by several predictors at different stages of the project are compared with the measured responses of sloping deposit specimens tested in a rigid box at six different centrifuge facilities around the world. The comparisons are presented for three rounds of simulations labeled here as types A, B, and C simulations. The type A simulations involved the response of the soil specimen to a prescribed base excitation with a maximum amplitude of 0.15 g (Motion #2). Comparisons of the numerical simulations with the experimental results show that a sub-set of type A simulations were in reasonably good agreement with the responses measured in the reference centrifuge experiment. The predictors subsequently assessed the performance of their type A simulations by comparing them to the measured responses, made the necessary adjustments in their models, and conducted a type B simulation of the response of the same soil specimen subjected to an amplified base excitation with a maximum amplitude of 0.25 g (Motion #4). In these type B simulations, the achieved base motions were used and the simulations showed an improved correlation with the experimental results. The predictors also conducted a type C simulation of the original test (Motion #2) using the base motions achieved on the six centrifuge facilities. The results showed very good agreement with the experimental results. Highlights: Details of the LEAP-2015 centrifuge tests are outlined. Class A numerical predictions are compared to the results of the centrifuge test conducted at RPI. Class B and C simulations of the centrifuge tests are compared with the experimental data. Detailed assessments are performed for each of the simulation sets.